TESL Trainee Teachers’ Experiences And Challenges During Practicum - Mohamad Yusof, Nurdiyana; Zainudin, Eilina Nasywa; Jaffari Din, Nur Najwa Hana (Selangor Humaniora Review, 2023)
The teaching practice facilitates the introduction of aspiring trainee teachers to the teaching profession, which eventually directs their professional advancement. This study examines and clarifies the experience future teachers have during their teaching practicum. The study sample consisted of TESL trainee teachers who had completed their four months of teaching practicum. A qualitative research design is implemented and an in-depth interview served as the source of data collection. A sample of 33 TESL trainee teachers were interviewed and the thematic analysis of the data are discussed in the findings. Based on the findings, three themes that arose and best explained the codes from the respondents' responses were classroom teaching, the trainee teachers' personal adjustments, and classroom management. The results demonstrated that the TESL trainee teachers had a fairly positive experience during their teaching practicum. Their responses contained several contradictions, notably with regard to their expectations of the key distinctions between real-world teaching and microteaching, as well as their time management in the classroom. Interpersonal to educational problems were some of the challenges and experiences encountered.